(untitled) - John J Barton (Reading, Massachusetts, 1994)
The book brings the power of C++ to science and engineering programming. IT builds on knowledge of both Fortran and C, the languages most familiar to scientists and engineers; systematically treats object-oriented programming, templates, and the C++ type system; relates the C++ programming process to expressing commonality in the design and implementation of programs; describes how to use existing FORTRAN and C subroutine libraries to implement C++ classes; introduces advanced techniques coordinating templates, inheritance, virtual function interfaces, and exceptions in substantive examples; provides example, including an extensive family of array classes, smart pointers, class wrappers for LAPACK, clesses for abstract algebra and dimensional analysis, function objects, exploiting existing C and FORTRAN libraries, automatic differentiation, and data analysis via nonlinear least squares using the singular value decomposition; references key sources of new programming ideas and C++ programming techniques
Keywords: c++ ( computer program language )